Effects of combined exercise and manual therapy on pain and physical function in overweight older adults with knee osteoarthritis: A randomized controlled trial - Seyed Ehsan Hosseini (Sport, Exercise, and Injury, 2026)
Background: Knee osteoarthritis (KOA) is a prevalent musculoskeletal disorder that leads to pain, reduced mobility, and functional limitations, particularly among overweight older adults. While exercise therapy is widely recommended as a primary non-pharmacological intervention, its effectiveness as a standalone approach may be limited due to increased biomechanical stress in this population. Objectives: This study aimed to evaluate and compare the effectiveness of exercise therapy alone and a combination of exercise and manual therapy on pain, joint function, range of motion (ROM), and physical performance in overweight older adults with KOA. Methods: A randomized controlled trial design was employed, involving 40 participants who were randomly allocated (1:1 ratio) using a computer-generated simple randomization sequence. Forty overweight older adults (mean age 58.3 ± 4.9 years; BMI 34.8 ± 3.2 kg/m²) with clinically diagnosed KOA participated in the study. Both groups underwent a 12-session physiotherapy program. Data were collected using the Visual Analog Scale (VAS) for pain, WOMAC for joint function, goniometry for ROM, and the Timed Up and Go (TUG) test for physical performance. Statistical analysis was conducted using JASP, including descriptive statistics, independent-samples t-tests, paired-samples t-tests, repeated-measures ANOVA, and ANCOVA to control for potential confounders. Results: Both groups demonstrated significant improvements in all outcome measures. Compared with exercise alone, the combined intervention resulted in greater pain reduction (adjusted mean difference = -1.07 points, p < 0.001, η² = 0.52), greater improvement in knee ROM (p < 0.001, η² = 0.61), and better TUG performance (p = 0.001, η² = 0.46). No significant between-group difference was observed for WOMAC scores (p = 0.234, η² = 0.03). Conclusions: The combination of exercise and manual therapy is more effective than exercise alone in improving pain and physical performance in overweight older adults with KOA. A multimodal physiotherapy approach is recommended to optimize rehabilitation outcomes in this population.